2005
DOI: 10.1007/s11103-005-2161-y
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the E-function for Floral Organ Identity in Rice Revealed by the Analysis of Tissue Culture-induced Loss-of-Function Mutants of the OsMADS1 Gene

Abstract: Rapid progress in studies on flower development has resulted in refining the classical 'ABC model' into a new 'ABCDE model' to explain properly the regulation of floral organ identity. Conservation of E-function for flower organ identity among the dicotyledonous (dicot) plants has been revealed. However, its conservation in monocotyledonous (monocot) plants remains largely unknown. Here, we show the conservation of E-function in rice (Oryza sativaL.) by characterizing tissue culture-induced mutants of two MADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 37 publications
4
129
0
Order By: Relevance
“…Under noninductive conditions, when OsMADS1-DGR is sequestered in the cytoplasm, we observe that florets recapitulate strong loss-offunction OsMADS1 mutant phenotypes (Fig. 2, B-E; Jeon et al, 2000;Agrawal et al, 2005;Prasad et al, 2005). The outer floret organs, lemma and palea, were narrow, poorly developed, and failed to enclose the inner organs (Fig.…”
Section: Loss-of-function Phenotypesmentioning
confidence: 77%
See 1 more Smart Citation
“…Under noninductive conditions, when OsMADS1-DGR is sequestered in the cytoplasm, we observe that florets recapitulate strong loss-offunction OsMADS1 mutant phenotypes (Fig. 2, B-E; Jeon et al, 2000;Agrawal et al, 2005;Prasad et al, 2005). The outer floret organs, lemma and palea, were narrow, poorly developed, and failed to enclose the inner organs (Fig.…”
Section: Loss-of-function Phenotypesmentioning
confidence: 77%
“…They contribute to panicle morphology, spikelet and FM specification, floral organ differentiation, and meristem determinacy (Jeon et al, 2000;Prasad et al, 2005;Cui et al, 2010;Gao et al, 2010;Kobayashi et al, 2010). Rice LEAFY HULL STERILE (LHS1)/OsMADS1, a member of the grass subgroup of LOFSEP genes, referred to henceforth as OsMADS1, is expressed in FMs, functions during FM establishment and floret organ patterning, and contributes to meristem termination (Jeon et al, 2000;Prasad et al, 2001Prasad et al, , 2005Agrawal et al, 2005;Ohmori et al, 2009;Cui et al, 2010;Gao et al, 2010;Li et al, 2010;Wang et al, 2010). In addition to studies on mutants in rice SEP factors, their protein-protein interactions are reported from yeast two-hybrid analyses.…”
mentioning
confidence: 99%
“…In rice, the B class gene SPW1 (OsMADS16) [20] and the C class genes OsMADS3 and OsMADS58 [21], as well as the D class gene OsMADS13 play critical roles in specifying inner floral organ and meristem identities. OsMADS1/LHS1 has been shown to be a SEP-like gene that is required for determining identity of the lemma/ palea and the meristem of inner floral organs [25][26][27][28][29]. It is possible that OsMADS6 interacts with other MADSbox protein(s) controlling rice flower development.…”
Section: Osmads6 Is a Key Regulator Specifying Floral Organ Identitiesmentioning
confidence: 99%
“…Obviously OsMADS6 plays a distinct role in specifying floral organ development from OsMADS1 in rice. Mutations or knockdown of OsMADS1 in rice result in elongated leafy lemma/palea, glume-like organs, a decreased number of stamens, and occasionally, extra pistils or florets [25][26][27][28][29], while mutations of OsMADS6 cause the homeotic transformation of paleas to lemma-like organs, lodicules and stamens into glume-like or mosaic structures. OsMADS6 and Os-MADS1 are both expressed in young floral meristems.…”
Section: Osmads6 Specifies 'Floral State' Together With Os-mads1mentioning
confidence: 99%
See 1 more Smart Citation